An empirical investigation of the relation between emotional intelligence and job satisfaction in the Lebanese service industry - Dagher, Grace K. (2010)
The escalating popularity of the Emotional Intelligence concept along with the increase in life/work outcomes that it is supposed to affect has lead researchers to scientifically investigate its relation to several of these outcomes. The purpose of this study is to investigate the role of emotional intelligence as a determining factor in several facets of job satisfaction among employees within the service sector. The results of this study provide insights to both practitioners and academicians on how employees’ attitudes can be influenced by non-cognitive factors. Further future studies and limitations of the study are discussed. Recently the concept of emotional intelligence (EI) has received a great deal of interest and fuelled much controversy. If anything, the interest in EI seems to be on the rise, and the unusual speed by which research on this subject is growing maybe addressed to the reason that scores on EI measures are associated with a number of real life outcomes (Grewal and Salovey, 2005). EI has been linked to a variety of outcomes from health to career success and life satisfaction etc... (CartWright and Pappas, 2008). In an organizational setting, the interest in EI is a result of the desire to interpret the differences in occupational success between people which cannot be explained by existing cognitive measures such as IQ alone (Zeidner et al., 2004). Several empirical studies have shown that IQ and other tests for cognitive ability account for a no more than 25% of the variance in work performance outcomes (Cherniss et al., 2006; CartWright and Pappas, 2008), other studies push the number down even further to 10% as a more realistic number (CartWright and Pappas, 2008). The low predictive power of cognitive tests and other problems accompanying them (e.g. group differences) sparked interest in non-cognitive predictors for personnel selection and attitudes. Personality tests were proved beneficial to use, but when used in isolation their validity was even lower than cognitive ability tests (Van Rooy et al., 2005). EI seemed to be a powerful tool as a growing body of recent research based on different models of EI suggests an incremental validity of EI over both traditional cognitive intelligence tests and personality tests (CartWright and Pappas, 2008). The use of EI measures for placement and selection is gaining momentum as companies realise the potential value of EI skills. The American Society for Training and Development estimates that four out of five companies are trying to improve productivity, customer service and manager performance by increasing their employees’ EI (Zeidner et al., 2004; CartWright and Pappas, 2008). The purpose of this study is to investigate the role of emotional intelligence as a determining factor in several facets of job satisfaction among employees within the service sector in Lebanon. The objectives can be summarized as mainly: providing a comprehensive study of emotional intelligence and job satisfaction as concepts, and examining the relationship between employee emotional intelligence and factors of employee job satisfaction. There have been many definitions of EI each based on the different understandings of what the concept is. In 1990 Salovey and Mayer defined EI as “ the subset of social intelligence that involves the ability to monitor one’s own and others’ feelings and emotions, to discriminate among them, and to use this information to guide one’s thinking and action” (Salovey and Mayer, 1990, p. 189). Later Mayer and Salovey introduced a refined definition of EI as “the capacity to reason about emotions, and of emotions to enhance thinking. It includes the abilities to accurately perceive emotions, to access and generate emotions so as to assist thought, to understand emotions and emotional knowledge, and to reflectively regulate emotions so as to promote emotional and intellectual growth” (Mayer and Salovey, 1997, p.10). This later definition is perhaps the most widely accepted scientific definition of EI and perhaps the most workable contemporary definition of EI (Zeidner et al., 2004). Another definition of EI was presented by Goleman in his bestselling book “Emotional Intelligence” in which he defines EI as consisting of “abilities such as being able to motivate oneself and persist in the face of frustration, to control impulses and delay gratification, to regulate one’s moods and keep distress from swamping the ability to think, empathise and to hope” (Goleman, 1995, p.34). As part of his definition, Goleman describes over 25 learned competencies, skills and abilities which constitute EI (CartWright and Pappas, 2008). Further refinements to this definition broadened the concept to include a wide range of personality characteristics and behavioural competencies giving the notion that Goleman defines EI as any desirable feature of personal character not represented by cognitive intelligence (Zeidner et al., 2004)